Belatacept during pregnancy in renal transplant recipients: Two case reports. Issue 8 (3rd June 2018) - Combs, Jenna; Kagan, Anna; Boelkins, Mark; Coscia, Lisa; Moritz, Michael; Hofmann, R. Michael
Abstract : Impaired fertility is common among patients with chronic organ failure, including end‐stage renal disease (ESRD). Women of childbearing age undergoing transplantation may experience rapid return of fertility. Pregnancy posttransplant presents numerous risks for the patient, fetus, and allograft. Maternal risks include hypertension and preeclampsia. Allograft risks include acute rejection and failure of the organ, and fetal risks include miscarriage, birth defects from immunosuppressants, premature delivery, and low birth weight. Belatacept, a selective T cell costimulation blocker, was approved for use in kidney transplant recipients in the United States in 2011. Little is known about the safety of belatacept during pregnancy in humans. We describe 2 cases of successful pregnancy and delivery with the use of belatacept‐based immunosuppression. The Transplant Pregnancy Registry International (TPR) is a voluntary registry for transplant recipients who have had pregnancies or fathered a pregnancy posttransplant. To date, these 2 cases are the only known exposures to belatacept that have been reported to the TPR.1 Abstract : The authors discuss the cases of two renal transplant recipients who received belatacept‐based immunosuppression prior to and throughout pregnancy.